2021
DOI: 10.1007/s10646-021-02431-4
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione S-transferase (PxGST2L) may contribute to the detoxification metabolism of chlorantraniliprole in Plutella xylostella(L.)

Abstract: The diamondback moth (Plutella xylostella L.), is an economic pest of cruciferous plants worldwide, which causes great economic loss to cruciferous plants production. However, the pest has developed resistance to insecticides. One of such insecticides is chlorantraniliprole. The study of the mechanisms underlying resistance is key for the effective management of resistance. In this study, a comparative proteomics approach was used to isolate and identify various proteins that differed between chlorantranilipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…For examples, CpGSTd1 expressed higher in fat body and silk gland of C. pomonella , CsGSTe4 and CsGSTu1 are primarily expressed in fat body and midgut of C. suppressalis (Liu et al, 2014; Meng et al, 2022). Using RNAi combined with bioassay, a lot of GST genes have been demonstrated to involve in the detoxification metabolism and susceptibility of insecticides, such as CpGSTd1 in lambda‐cyhalothrin detoxification of C. pomonella (Liu et al, 2014), DcGSTe2 in the detoxification metabolism of fenpropathrin in Diaphorina citri (Yu & Killiny, 2018), the PxGST2L in chlorantraniliprole‐resistant P. xylostella (Yin et al, 2021) and CsGSTe4 and CsGSTu1 in the abamectin‐resistant of C. suppressalis (Liu et al, 2014; Meng et al, 2022). The sensibility of G. molesta larvae was obviously increased when knockdown of GmGSTo2 , GmGSTs1 and GmGSTz1 after exposure with EB, CT and LC compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, CpGSTd1 expressed higher in fat body and silk gland of C. pomonella , CsGSTe4 and CsGSTu1 are primarily expressed in fat body and midgut of C. suppressalis (Liu et al, 2014; Meng et al, 2022). Using RNAi combined with bioassay, a lot of GST genes have been demonstrated to involve in the detoxification metabolism and susceptibility of insecticides, such as CpGSTd1 in lambda‐cyhalothrin detoxification of C. pomonella (Liu et al, 2014), DcGSTe2 in the detoxification metabolism of fenpropathrin in Diaphorina citri (Yu & Killiny, 2018), the PxGST2L in chlorantraniliprole‐resistant P. xylostella (Yin et al, 2021) and CsGSTe4 and CsGSTu1 in the abamectin‐resistant of C. suppressalis (Liu et al, 2014; Meng et al, 2022). The sensibility of G. molesta larvae was obviously increased when knockdown of GmGSTo2 , GmGSTs1 and GmGSTz1 after exposure with EB, CT and LC compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme activities can play a key role in understanding the patterns of resistance and insect susceptibility to chemicals [38]. Many previous reports found that P450, EST and GST were commonly the primary detoxification enzymes that help insect pests degrade a different type of xenobiotic [39][40][41]. Our results indicated that significant differences existed in the activity of detoxification enzymes between different populations.…”
Section: Discussionmentioning
confidence: 56%
“…Studies have shown that CAP resistance is related to the expression level or activity of GSTs. Knockdown of PxGST2L increased the toxicity of CAP to the diamondback moth 60 . There is a strong correlation between GST enzyme activity and resistance to CAP in P. xylostella 61 .…”
Section: Discussionmentioning
confidence: 95%
“…Knockdown of PxGST2L increased the toxicity of CAP to the diamondback moth. 60 There is a strong correlation between GST enzyme activity and resistance to CAP in P. xylostella. 61 CAP induced the mRNA level of a sigma class GST gene in the Asiatic rice borer, Chilo suppressalis.…”
Section: Discussionmentioning
confidence: 97%